Contact between first dynasty Egypt and specific sites in the Levant: New evidence from ceramic analysis. (April 2019) - Iserlis, Mark; Steiniger, Daniel; Greenberg, Raphael
Abstract: New optical mineralogy and pXRF studies of ceramics from First Dynasty royal tombs at Abydos and from Tel Bet Yerah, in the Jordan Valley, reveal a very close correlation between vessels from Egypt and both fired and unfired wares from a potter's establishment at Tel Bet Yerah, marking the first time that vessels found in Egypt can be attributed a site-specific origin in the Levant. Other vessels, most of them previously identified as 'metallic ware', included some that likely originated in the northern Jordan Valley and two vessels from a the Lebanese Biqâ valley or Lebanese coast. The vessels found in Egypt most likely span the entire First Dynasty, beginning with Djer, whereas the equivalent material from Tel Bet Yerah falls in the EB II/ESL 4 period, radiometrically dated at Bet Yerah to ca. 3100–2900 BCE. No evidence was found for a more southerly origin of imported Levantine wares in the First Dynasty. Highlights: OM and pXRF analyses were conducted on imported vessels in 1st Dynasty royal tombs. For the first time, they can be matched to specific industries in the central Levant. These include Levantine Metallic Ware and unfired products from Tel Bet Yerah. Coevolution of Levantine ceramic industries and royal Egyptian trade is indicated. Targeted provenance can identify hubs and networks of early Mediterranean commodities.